"Wait and See" Approach to the Emergency Department Cardioversion of Acute Atrial Fibrillation. (17th November 2011) - Doyle, Brian; Reeves, Mark
Abstract : Objective . Acute atrial fibrillation often spontaneously resolves. This study aimed to investigate the outcomes and satisfaction of an evidence-based ED protocol employing a "wait and see" approach. Methods . A prospective observational cohort study of adult patients presenting to the Emergency Department with stable acute atrial fibrillation was performed. Patients were excluded if they were considered to be unstable, need hospitalization, or poor candidates for ED procedural sedation. Routine care was provided on the index visit, and suitable candidates were discharged and asked to return to the ED the following day for possible electrical cardioversion. Outcome measures included spontaneous reversion to sinus rhythm, success of cardioversion, length of stay, adverse event and return visits for AF within 30 days, and patient satisfaction. Results . Thirty five patient encounters were analysed over a 21-month period. Twenty two of the 35 patients (63%) had spontaneous resolution of atrial fibrillation upon presentation for potential cardioversion. All of the remaining patients underwent successful cardioversion to normal sinus rhythm without significant adverse events recorded. No patients required hospitalization. Three patients (9%) returned to the ED within 30 days for recurrence of atrial fibrillation. All patients were reported to be "very satisfied" with this approach. Conclusion . A "wait and see" approach to the ED electrical cardioversion of atrial fibrillation showed that almost two-thirds of patients had spontaneous resolution without requiring cardioversion or observation in the ED or hospital. All patients were successfully reverted to normal sinus rhythm and had a high degree of satisfaction.